The clinical efficacy and safety of acupuncture intervention on cancer-related insomnia: A systematic review and meta-analysis - Yu, HaiXin; Liu, CaiYun; Chen, Bo; Zhai, JingBo; Ba, DongSheng; Zhu, Zheng; Li, NingCen; Loh, PeiYong; Chen, AoXiang; Wang, Bin; Guo, Yi; Liu, YangYang; et al. (Frontiers in Neuroscience, 2022)
Objective To evaluate the efficacy and safety of acupuncture in treating symptoms for Cancer-related Insomnia(CRI) patients. Methods Seven databases were searched from the time of database establishment to 31 March 2022. Randomized Controlled Trials (RCTs) on acupuncture intervention for CRI were collected. Literature screening and data extraction were performed independently by two researchers. Meta-analysis was performed using RevMan 5.4 software. Results A total of 13 articles with 1,109 participants were included. Five hundred and seventeen in the treatment group and 592 in the control group. Ten of the RCTs used the PSQI rating scale and four randomized controlled trials used the ISI rating scale, and the PSQI and ISI were analyzed together as continuous data. The results of the meta-analysis were: MD = −1.83, 95%CI = [−2.71, −0.94], P < 0.0001, indicating a significant improvement in PSQI scores in patients with CRI by acupuncture intervention; MD = 0.79, 95%CI = [−0.46, 2.03], P = 0.22. Acupuncture was not statistically significant on ISI scores for patients with CRI compared to controls, which does not yet indicate that acupuncture is effective for symptoms in patients with CRI. The results of the meta-analysis of the other 4 items using sleep disorder logs as efficacy analysis data were as follow, relative risk RR = 0.47, 95%CI = [0.33, 0.66], P < 0.0001. The difference was statistically significant, indicating that acupuncture can improve the symptoms of CRI patients compared to control group. Conclusion Acupuncture can improve the symptoms of patients with CRI to some extent, but due to the relatively small number and low quality of the included literature in this study, more high-quality clinical trials are needed as supplement the evidences in future. Systematic review registration https://www.crd.york.ac.uk/prospero/.